2021
DOI: 10.1021/acs.energyfuels.1c01417
|View full text |Cite
|
Sign up to set email alerts
|

NMR Investigation of Brine Imbibition Dynamics in Pores of Tight Sandstones under Different Boundary Conditions

Abstract: This study explores imbibition dynamics and flowback of fracturing fluids in Penglaizhen sandstones by imbibition experiment and nuclear magnetic resonance analysis. A gas–water system was considered and samples were subjected to different boundary conditions and fully immersed in the wetting phase for imbibition. A close range of the pore radius was observed between 0.1 nm and 9.3 μm for all samples. Basic features of the imbibition phases were represented by the imbibition profile, and imbibition parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
7
3
Order By: Relevance
“…The forced imbibition dynamics of shale with different boundaries in this study are quite different from the spontaneous imbibition dynamics under ASO, TSO, and OSO boundaries obtained by Umeobi et al . and Yang et al Umeobi et al found that the shale spontaneous imbibition flow in all boundary conditions are contributions of both the capillary pressure and diffusion. Imbibition in AFO is predominantly by the capillary pressure with negligible diffusion, but imbibitions of TSO and OSO are predominantly by diffusion imbibition.…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…The forced imbibition dynamics of shale with different boundaries in this study are quite different from the spontaneous imbibition dynamics under ASO, TSO, and OSO boundaries obtained by Umeobi et al . and Yang et al Umeobi et al found that the shale spontaneous imbibition flow in all boundary conditions are contributions of both the capillary pressure and diffusion. Imbibition in AFO is predominantly by the capillary pressure with negligible diffusion, but imbibitions of TSO and OSO are predominantly by diffusion imbibition.…”
Section: Discussioncontrasting
confidence: 95%
“…32,33 Moreover, the values of imbibition potential are such that TSO > ASO > HSO > OSO, illustrating the different contributions made by late imbibition stages to the whole forced imbibition process. However, these findings are contrary to the previous studies, 31,32,59 which can be attributed to the intrinsic differences of imbibition mechanisms between spontaneous imbibition and forced imbibitions coupled with the boundaries. 4.5.…”
Section: Comparison Of the Imbibition Parameters Of Four Boundariescontrasting
confidence: 99%
See 3 more Smart Citations